Colourimetric image analysis as a diagnostic tool in female genital schistosomiasis. Issue 3 (March 2015) - Holmen, Sigve Dhondup; Kjetland, Eyrun Floerecke; Taylor, Myra; Kleppa, Elisabeth; Lillebø, Kristine; Gundersen, Svein Gunnar; Onsrud, Mathias; Albregtsen, Fritz
Highlights: We describe a new method for detecting lesions caused by genital schistosomiasis. Region of interest is automatically detected and mucosal reflections are masked. Mean colour values are measured to correct for heterogeneous images. An adaptive colourimetric algorithm detects lesions. We found that the method may yield a sensitivity and specificity of 83% and 73%. Abstract: Female genital schistosomiasis (FGS) is a highly prevalent waterborne disease in some of the poorest areas of sub-Saharan Africa. Reliable and affordable diagnostics are unavailable. We explored colourimetric image analysis to identify the characteristic, yellow lesions caused by FGS. We found that the method may yield a sensitivity of 83% and a specificity of 73% in colposcopic images. The accuracy was also explored in images of simulated inferior quality, to assess the possibility of implementing such a method in simple, electronic devices. This represents the first step towards developing a safe and affordable aid in clinical diagnosis, allowing for a point-of-care approach.